2020
DOI: 10.1007/s10877-020-00582-z
|View full text |Cite
|
Sign up to set email alerts
|

Physiological effects of two driving pressure-based methods to set positive end-expiratory pressure during one lung ventilation

Abstract: During one-lung ventilation (OLV), titrating the positive end-expiratory pressure (PEEP) to target a low driving pressure (∆P) could reduce postoperative pulmonary complications. However, it is unclear how to conduct PEEP titration: by stepwise increase starting from zero PEEP (PEEP INCREMENTAL) or by stepwise decrease after a lung recruiting manoeuvre (PEEP DECREMENTAL). In this randomized trial, we compared the physiological effects of these two PEEP titration strategies on respiratory mechanics, ventilation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…At present, the PEEP titration based on lung compliance has two methods: incremental titration and decremental titration. Previous study shown that both the incremental titration and decremental titration were able to decrease intraoperative shunt, but only the decremental titration improved oxygenation and lowered driving pressure [14]. Our previous study suggested that the decremental PEEP titration can improve respiratory mechanics, oxygenation parameters, and the inflammatory reaction during one-lung ventilation [10].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…At present, the PEEP titration based on lung compliance has two methods: incremental titration and decremental titration. Previous study shown that both the incremental titration and decremental titration were able to decrease intraoperative shunt, but only the decremental titration improved oxygenation and lowered driving pressure [14]. Our previous study suggested that the decremental PEEP titration can improve respiratory mechanics, oxygenation parameters, and the inflammatory reaction during one-lung ventilation [10].…”
Section: Discussionmentioning
confidence: 89%
“…The PBW was calculated according to a predefined formula:50 + 0.91 × (centimeters of height-152.4) for men and 45.5 + 0.91 × (centimeters of height-152.4) for women. The incremental PEEP titration [14] was performed two times in VI and PI group. In both groups, the first incremental PEEP titration was performed immediately after intubation, and the individualized PEEP level was set and maintained until the establishment of pneumoperitoneum.…”
Section: Ventilation Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…In a more nuanced approach to setting optimal PEEP during ventilation of only one lung while monitoring lung mechanics and oxygenation, Spadaro et al [ 18 ] investigated whether it is better to titrate by increasing PEEP incrementally from a pressure of zero up to 16 cmH 2 O, or by decreasing it decrementally from 16 cmH 2 O after recruiting the lungs with a deep inflation. Both approaches proved beneficial, but only the decremental titration strategy improved oxygenation and reduced the swings in airway pressure needed to ventilate the lungs.…”
Section: Monitoring To Guide Peep Settings During Surgerymentioning
confidence: 99%
“…Relevant studies have shown that lower driving pressure could decrease lung overstress and was associated with lower mortality in patients with ARDS [ 14 17 ]. However, the increased risk of poor prognosis associated with high drive pressure has been observed not only in patients with ARDS but also in ventilated patients, which includes patients with severe pneumonia without ARDS [ 18 ] and surgical patients with healthy lungs during the perioperative period [ 19 21 ]. Even so, studies on driving pressure and patients with HF are limited.…”
Section: Introductionmentioning
confidence: 99%